Sulfur reduction in acid rock drainage environments - Florentino, Anna P. (2015)
Microbiological suitability of acidophilic sulfur reduction for metal recovery was explored by enriching sulfur reducers from acidic sediments at low pH (from 2 to 5) with hydrogen, glycerol, methanol and acetate as electron donors at 30 °C. The highest levels of sulfide in the enrichments were detected at pH 3 with hydrogen and pH 4 with acetate. Cloning and sequencing of the 16S rRNA gene showed dominance of the deltaproteobacterial sulfur-reducing genus Desulfurella in all the enrichments and subsequently an acidophilic strain (TR1) was isolated. Strain TR1 grew at a broad range of pH (37) and temperature (2050 °C) and showed good metal tolerance (Pb2+, Zn2+, Cu2+, Ni2+), especially for Ni2+ and Pb2+, with maximal tolerated concentrations of 0.09 and 0.03 mM, respectively. Different sources of sulfur were tested in the enrichments, from which biosulfur showed fastest growth (doubling time of 1.9 days), followed by colloidal, chemical and sublimated sulfur (doubling times of 2.2, 2.5, and 3.6 days, respectively). Strain TR1?s physiological traits make it a good candidate to cope with low pH and high metal concentration in biotechnological processes for treatment of metal-laden acidic streams at low and moderately high temperature.